HUBUNGAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS SEBATUNG - Musfida, Nur Hikmah; Hateriah, Siti (LPPM Universitas Sari Mulia, 2023)
Background: Pregnant women generally require additional nutrients; however, deficiencies commonly occur in energy, protein, and minerals such as iron and potassium. Iron deficiency can lead to several health problems, including anemia. According to the World Health Organization (WHO), 40% of pregnant women worldwide experience anemia. The prevalence of anemia among pregnant women is 14% in developed countries and 51% in developing countries, with 50% of cases attributed to iron deficiency anemia. Dietary intake during pregnancy significantly affects the nutritional status of pregnant women, which in turn has a major impact on fetal growth and development. Objective: This study aims to determine the relationship between nutritional status and the incidence of anemia in pregnant women at the Sebatung Health Center. Method: This research is a quantitative study using a descriptive-analytic method with a cross-sectional design. Secondary data were obtained from the antenatal care register. The sample consisted of 46 first-trimester pregnant women selected through purposive sampling, all of whom had undergone Mid-Upper Arm Circumference (MUAC) and hemoglobin level examinations. Data were analyzed using the Spearman correlation test. Results: The highest percentage was found among pregnant women with normal nutritional status and no anemia (85.7%), followed by those with normal nutritional status but with anemia (72.2%). Pregnant women with Chronic Energy Deficiency (CED) and anemia accounted for 27.8%, while the lowest percentage was among those with CED but without anemia (14.3%). The Spearman correlation test showed a correlation coefficient of 0.317 with a significance value of 0.032 (p < 0.05), indicating a significant relationship between nutritional status and the incidence of anemia in pregnant women. Keywords: anemia, pregnant women, nutritional status.